Student management system in schools: The use of web-based application / Mahfudzah Othman, Zainab Othman and Mohd Norafizal A. Aziz - Othman, Mahfudzah; Othman, Zainab; A. Aziz, Mohd Norafizal (Universiti Teknologi MARA Cawangan Pahang, 2006)
The study was carried out to introduce the use of database management system as a medium to enhance record keeping for students' documents in schools around Bandar Jengka, Pahang. It explored the uses of web-based application technologies that feature various benefits such as improving information sharing among users in dispersed locations and facilitating quick response to information queries, updates, reports and many other processes. This high-end technology comprises different types of applications such as MySQL as the relational database, the hypertext transfer protocol (PHP) and the Apache web server. In this study, the System Development Research Methodology was used as a guideline to the overall development of the prototype system. The benefits of these technologies are discussed in this paper. The Student Management System may contribute to a more comprehensive record keeping method in schools.